Umpasa in Batak Toba Wedding Ceremony in Medan: Meaning and Tradition of Berpantun - Pangaribuan, Rotua; Sihite, Jubilezer; Marbun, Juliaster; Manurung, Naomi Suryana; Batubara, Junita; Pasaribu, Tiara (Journal of English Language and Education, 2024)
This study aims to document and analyze the role of umpasa in Batak Toba wedding ceremonies and provide younger generations with a deeper understanding of the importance of preserving wedding traditions. This study explores the cultural significance of umpasa, the traditional poetic expressions used in Batak Toba weddings, and their impact on the overall ceremony. By examining the historical context and contemporary usage of umpasa, this research seeks to highlight the intrinsic connection between language, rituals, and cultural identity in Batak Toba society. Additionally, the findings contribute to the development of educational resources and cultural preservation initiatives aimed at ensuring the continuity of these cherished traditions for future generations.   The research method employed was an ethnographic study. Data were collected through participatory observations and semi-structured interviews with traditional leaders and families involved in wedding ceremonies. The findings reveal that umpasa plays a crucial social role as a tool for maintaining harmony, strengthening family solidarity, and passing cultural values on to future generations. However, interest in this tradition has declined over time, and more effort is needed to preserve it. This study is expected to enhance appreciation of the cultural richness of Batak Toba and inspire the preservation of umpasa traditions in the future.